Comparative Study on The Physiochemical and Nutritional Properties of Fresh Milk Samples Collected from Farms Animals in Benghazi City, Libya : Analysis of Physicochemical and Nutrition properties of raw milk samples from………………………… - Ahmida, Nagwa; Shaboun, Seham; Ahmida, Mohemed (Journal of Pure & Applied Sciences, 2021)
Milks in general is a complex system of colloidal dispersion of different components including minerals, carbohydrates, proteins and fats as major components and other minor components. The milk quality and nutritional contents can be demonstrated by evaluating the physiochemical properties of milk. This work carried out to evaluate and compare some physiochemical parameters and nutritional properties of fresh milk samples collected, from four animal species named cows, camels, goats and sheep, from different farms in Benghazi city, the eastern part of Libya and analyzed for the following parameters; pH, acidity, solid nonfat contents, specific denisty, water, ash, lactose, proteins and fats. The results of physiochemical properties showed that the highest pH and acidity was for goat milk (6.65 and 0.031%) respectively. While, the highest solid nonfat content was for sheep milk (12.96 %) and the highest specific density was for cow milk (1.502 g/cm3). The results of nutritional contents analysis showed that the sheep milk had the highest ash, lactose, total proteins (TP) and fats contents (0.87%), (7%), (5%) and (9%) respectively. While, the cow milk had the highest water contents (88%). The physiochemical properties and nutritional contents of milk samples vary according to animal species. The values of physiochemical properties, and nutritional contents, that obtained in this study were in agreement with the values of the same properties published in some international studies